Moderating effect of access to finance of the gem and jewelry industry - SHARIFF, M.N.M; AHMAD, N.R; SHABBIR, M.S (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This study aims to investigate the moderating effect of access to finance on the linkages between strategic orientations and small medium enterprises (SMEs) performance of the gem and jewelry industry in Thailand. The sample of this study consisted of 116 firms operating in the gem and jewelry business in Thailand. In this study that data were collected using the systematic sampling technique. Based on the obtained analysis results, positive and significant relationships were found between market orientation (MO), learning orientation (LO), and SMEs performance, while entrepreneurial orientation (EO) was not found to have a positive significant relationship with SMEs performance.